Membangun Hutan Lestari: Analisis Undang-undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Chandra, Febrian; Harmaini, Harmaini (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
The purpose of writing this scientific article is to identify and analyze management supervision in the forestry sector in general in the context of forest protection in industrial plantation forests, because the sustainable implementation of industrial plantation forests in principle requires government involvement in community activities through legal instruments. in the form of permits. Sometimes government policies regarding participation in community activities do not end in just one stage, but rather go through several policies. As a research method, a normative research method was used, the results of which are as follows: Because this is an industrial plantation forest, the special basic law, namely. H. Forestry Law no. 41 of 1999 and newer laws. Regional Government Law no. 23 of 2014. Although the Environmental Protection and Management Law no. 32 of 2009 has different content, because it relates to environmental permits in general. Industrial forest plantation permits, known as IUPHHK-HTI, are issued by authorized officials from the Minister of Environment and Forestry, taking into account recommendations from the governor where the permit is issued. In this case, the authorization procedure actually requires preventive checks, because preventive checks are to avoid possible errors with the ultimate goal of ensuring forest sustainability.